Adaptive Backstepping Control of SWISS Rectifier - WANGJitao; JIAYunfei; WANGYifei; GEMengna (Journal of Harbin University of Science and Technology, 2023)
Aiming at the weak dynamic anti disturbance performance of PI controlled Swiss rectifier , based on the state equation of the equivalent circuit of SWISS rectifier and combined with the basic principle of adaptive backstepping control , an adaptive backstepping controller of SWISS rectifier with load as the system uncertain parameter is designed , and its stability is proved. The simulation results show that compared with the traditional double closed-loop PI control , the adaptive backstepping control SWISS rectifier has better steady-state output characteristics and dynamic response performance against sudden load disturbance. The hardware in the loop experimental platform of box further verifies the correctness of the simulation results and the effectiveness of the adaptive backstepping control strategy.